Phospholipids in non-alcoholic fatty liver disease - V. V. Skvortsov; M. V. Lunkov; R. Sh. Tinaeva; E. M. Skvortsova (Медицинский совет, 2022)
Non-alcoholic fatty liver disease, or NAFLD – is a pathology that usually has a metabolic cause and is not caused by excessive alcohol consumption. NAFLD is the most frequent chronic liver disease worldwide and is accompanied by a high financial burden for the patient and the healthcare system. NAFLD is generally considered a “benign disease” with low progression to fibrosis, cirrhosis, and hepatocellular carcinoma (HCC). Nevertheless, due to the large number of affected patients, the prevalence of cirrhosis of the liver has gradually increased, and in fact it represents the third cause of liver transplantation in the world. Moreover, even if the frequency of HCC in patients with NAFLD is lower than in patients with HCV/HBV cirrhosis, the absolute number of HCC associated with NASH is higher due to the higher number of patients with NAFLD. It is likely that the importance of this disease will continue to grow in the future, when new treatments and prevention programs for hepatitis C and B reduce the size of viral liver infections. Many aspects of the disease have yet to be solved. It is very important to understand the mechanisms underlying the occurrence and development of NAFLD, the features of the clinic and diagnosis, as well as the tactics of management and treatment of patients with non-alcoholic fatty liver disease. It is important for patients to get a complete understanding of NAFLD so that they can play an active role in the treatment of their disease.